Regulation of Spontaneous Propagating Waves in the Embryonic Mouse Brainstem - Bosma, Martha M. (Frontiers in Neural Circuits, 2017)
Spontaneous activity modulates many aspects of neural development, including neuronal phenotype, axon path-finding and synaptic connectivity. In the embryonic mouse brainstem, spontaneous activity initially is recorded in isolated cells at embryonic day (E) 9.5, and 48 hours later takes the form of propagating waves. The majority of these waves originate from one midline initiation zone (InZ), which is situated within the developing serotonergic raphe. InZ cells express a t-type calcium channel, are depolarized, and have high membrane resistance, the combination of which allows spontaneous depolarization. Propagating events require signaling at metabotropic 5-HT receptors; a possible source could be 5-HT released by newly differentiating 5-HT neurons. At E11.5, waves propagate throughout the hindbrain, with some events crossing into the midbrain. At E12.5, lateral cells (further than 150 μm from the midline) up-regulate expression of a K channel that increases resting conductance and hyperpolarizes them, preventing the propagation of waves laterally. At the same stage, cells in the isthmus up-regulate t-type calcium channels, permitting more events to cross into the midbrain, some of which form recurring loops of activity that are able to keep intracellular calcium levels high for many minutes. At E13.5, caudal hindbrain cells hyperpolarize utilizing the same K conductance, and 24 hours later, at E14.5, the InZ hyperpolarizes and no longer undergoes spontaneous events. Thus, 5-HT receptor-dependent propagating waves in the embryonic brainstem are generated and propagated by regulation of membrane conductance. We discuss these mechanisms, and the possible role of this spontaneous activity in neuronal development.